Analysis of factors affecting the success of pupil’s education (The Journal of Psychology and Sociology, 2017)
This article analyze the reasons for pupil’s poor progress from the point of view of psychology, pedagogy and neuropsychiatric processes of the child’s organism, highlights the important role of the basic factors in the mental development of the child, the need for neuropsychological diagnostics, as well as the activities of correctional and developmental work. Currently, due to the complexity of the educational programs, increasing the flow of information, the entire amount of underachieving students increasing. One of the reasons for poor progress of pupils is the low level of development of cognitive functions. Problems unformed cognitive functions are more related to the insufficient development of the basic factors of mental development, which is a necessary step to overcome the difficulties of learning. The importance of using neuropsychological approach to the diagnosis of the state of higher mental functions is one of the main instruments of early detection of the causes of the cognitive process unformed, in order to avoid the difficulties of children in the development of teaching material. Neuropsychological method solves the problem of identifying the causes and lag mechanism in child development, learning difficulties in school, studying aborted or delay the development of higher mental functions and their structural inferiority reveals failure of the work of certain areas of the brain functional or organic origin, that is, makes it possible to correlate the deviation or deficit in the child’s mental development of delayed maturation of the brain or other areas. In the future, correctional work, aimed at both the neuropsychological status of the child as a whole and to local issues (such as cognitive processes), matures and more complete functioning of morpho-functional foundations of mental processes, overcome, learning difficulties, improve school performance.Key words: junior pupil’s difficulties, psychological-pedagogical and neuropsychichological reasons for poor progress, basic factors of psychic development of child, motor correction.